2018
DOI: 10.1002/ejp.1324
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital opioid consumption, but not pain intensity scores, predicts 6‐month levels of pain catastrophizing following hepatic resection: A trajectory analysis

Abstract: Background The study aims were to model acute pain intensity and opioid consumption trajectories up to 72 hr after open hepatic resection, identify predictors of trajectory membership and examine the association between trajectory memberships and 6‐month pain and psychological outcomes. This is a long‐term analysis of a published randomized controlled trial on the impact of medial open transversus abdominis plane catheters on post‐operative outcomes. Methods A total of 152 patients (89 males; mean age 63.0 [ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
7
2
Order By: Relevance
“…Second, we used the numerical rating scale as a measurement tool of pain intensity, instead of analgesic consumption. Recent study has reported different trajectories between postoperative pain and opioid consumption 28. Although the validity and reliability of self-report pain rating scale have been verified in Chinese adults,29 biases may exist in some subpopulations 30.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, we used the numerical rating scale as a measurement tool of pain intensity, instead of analgesic consumption. Recent study has reported different trajectories between postoperative pain and opioid consumption 28. Although the validity and reliability of self-report pain rating scale have been verified in Chinese adults,29 biases may exist in some subpopulations 30.…”
Section: Discussionmentioning
confidence: 98%
“…Recent study has reported different trajectories between postoperative pain and opioid consumption. 28 Although the validity and reliability of self-report pain rating scale have been verified in Chinese adults, 29 biases may exist in some subpopulations. 30 Third, we did not analyse the adverse events of analgesic medication (eg, respiratory depression), and unintended bolus and malfunction of IV-PCA due to data unavailability.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…Several other studies have also identified that while anxiety or catastrophizing were associated with greater opioid use after surgery or during patients' hospitalizations, depression in fact was not. 6,20,21,38,40,45 While opioids should continue to be readily available to treat cancer-related pain, oncology care teams need to screen and treat psychological symptoms that cooccur with cancer pain because these symptoms are associated with worse pain outcomes and research has shown that psychological symptoms are risk factors for opioid misuse. 12,41 Future studies which explicitly investigate interactions between depression and other psychological symptoms in the treatment of cancer-related pain are merited.…”
Section: Discussionmentioning
confidence: 99%
“…22 Previous studies in patients with chronic noncancer pain suggest that higher psychological distress and pain catastrophizing are associated with worse pain outcomes, including during hospitalization. 21,38 Yet, to the best of our knowledge, no study has examined whether these and other salient factors are associated with worse pain outcomes among hospitalized cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, instead of the dosage of analgesics consumption, we used NRS, a self-reporting subjective pain scale, as a tool to evaluate pain intensity. Although NRS had been considered a valid, reliable, and appropriate tool, a recent study showed different trajectories between pain intensity scores and opioid consumption [ 44 ]. This is a potential confounder of our study.…”
Section: Discussionmentioning
confidence: 99%